Nuevo hallazgo de Miersia cornuta Phil. (Gilliesieae-Alliaceae) - Escobar, Inelia; Novoa, Patricio; Ruiz, Eduardo; Negritto, María; Baeza, Carlos (Gayana Botánica, 2010)
A new discovery of Miersia cornuta Phil. from Valparaiso Region, Chile, is presented. Details of flower and fruit has been unclear, what has caused this taxon has been considered a doubtful species. The complete description, commentaries, new localities of this endemic species, and a key for Miersia species are given.